Comparisons Between COVID-19 Stigma and Other Stigmas: Distinct in Explicit Attitudes and Similar in Implicit Process - Zhu, Jiajia; Yan, Lihua; Mu, Yan (Frontiers in Psychology, 2022)
Since the outbreak of COVID-19, the public stigma associated with COVID-19 has emerged. To better understand the COVID-19 stigma, the present research conducted three studies on 1,493 Chinese participants from the outbreak to the recovery period of the COVID-19 pandemic to examine the psychological mechanisms of COVID-19 stigma by comparing it with other disease-related stigmas in terms of their explicit and implicit processes. Study 1 and Study 2 jointly demonstrated that the public endorsed more stigma towards the COVID-19 related people (i.e., the COVID-19 patients) relative to the other disease-related people (i.e., the SARS patients, people with flu) in multiple explicit aspects, including emotional, motivational, cognitive, and social processing. Using the implicit association test (IAT), Study 3 found no significant difference in the implicit measures of the COVID-19 vs. the SARS groups, which further revealed that the pandemic stigmas (i.e., COVID-19 and SARS) were similar at the implicit level. These findings suggest common (implicit level) but distinct (explicit level) psychological processes of the pandemic-related stigmas, which provide reference to policymakers in formulating suitable interventions to deal with COVID-19 stigma and a newly generated potential stigma and provide psychological support for the public in the future.